PENGARUH LIKUIDITAS KECUKUPAN MODAL PROFITABILITAS DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDOENSIA - Sari, Dina Mustika; Suhartono, Suhartono; Ningsih, Ihdina Aulia (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to provide empirical evidence regarding the effect of liquidity, proxied by the loan to deposit ratio; capital adequacy, measured by the Capital Adequacy Ratio; profitability, proxied by return on assets; and managerial ownership on earnings management in banking companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research employs a quantitative approach using multiple linear regression analysis, processed with SPSS version 25. The population consists of 43 companies, and the sample was selected using a purposive sampling method, resulting in 55 observational data from 11 selected companies. After removing 3 outlier data, the final sample analyzed consisted of 52 data points. The results show that, partially, the loan to deposit ratio, return on assets, and managerial ownership have a positive and significant effect on earnings management. Conversely, the Capital Adequacy Ratio has a negative and significant effect on earnings management. Simultaneously, the loan to deposit ratio, Capital Adequacy Ratio, return on assets, and managerial ownership have a significant effect on earnings management.